Rekam Jejak Pangeran Aria Soeria Atmadja (Bupati Sumedang Tahun 1883-1919) - Rahmi Handayani; Erlina Wiyanarti; Leli Yulifar (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2019)
Pangeran Aria Soeria Atmadja was a Sumedang’s Regent figure who came from a royal family. When he became Sumedang’s Regent in 1883-1919, he received a lot of prizes from Netherland Colonial Government. This research highlighted the question, “How was the Role of Pangeran Aria Suriaatmadja as a Sumedang’s Regent in 1883-1919?”. During his leadership, Pangeran Aria Soeria Atmadja issued various policies to the Sumedang’s people, such as school development policy in the entire villages of Sumedang Regency, planting Palawija policy, the making of protected forest policy, themaking of upper-class bank and coaching for Sumedang civil servant dan its people. During 32 years of leadership, the prosperity of Sumedang’s people increased and had lots of impacts. Nevertheless, it is interesting to conduct a deeper study of Pangeran Aria Soeria Atmadja’s policies that brought prosperities to Sumedang’s people. This study is expected become a reference for other researchers that will conduct a study about the Role of Pangeran Aria Soeria Atmadja when he became Sumedang Regent because there are lots of aspects that have not explored further by the researcher.